Novel Antiatherosclerotic Therapies. Issue 4 (April 2019) - Libby, Peter; Everett, Brendan M.
Abstract : Many measures can control lipid risk factors for atherosclerosis. Yet, even with excellent control of dyslipidemia, other sources of risk remain. Hence, we must look beyond lipids to address residual risk. Lifestyle measures should form the foundation of cardiovascular risk control. Many pharmacological interventions targeting oxidation have proven disappointing. A large program tested inhibition of a LpPLA2 (lipoprotein-associated phospholipase A2 ), culminating in 2 large-scale clinical trials that did not meet their primary end points. A variety of antioxidants have not shown benefit in clinical trials. Numerous laboratory and clinical studies have inculpated inflammatory pathways in the pathogenesis of atherosclerotic events. The p38 MAPK (mitogen-activated protein kinase) inhibitor losmapimod and an inhibitor of a leukocyte adhesion molecule, P-selectin, did not alter adverse events in trials. Low-dose methotrexate, despite the promising observational studies, did not lower biomarkers of inflammation or alter cardiovascular outcomes in the CIRT (cardiovascular inflammation reduction trial). Four large-scale investigations underway will determine colchicine's ability to reduce recurrent events in secondary prevention. The CANTOS (Canakinumab Anti-inflammatory Thrombosis Outcomes Study) showed that an antibody that neutralizes IL (interleukin)-1β can reduce recurrent cardiovascular events in secondary prevention. The success of CANTOS points to the pathway that leads from the NLRP3 (NOD-like receptor family, pyrin domain-containing protein 3) inflammasome through IL-1β to IL-6 as an attractive target for further study and clinical development beyond lipid therapies to address the unacceptable burden of risk that remains despite our best current care in secondary prevention.